Consumption of ultra-processed foods on free sugar intake of Portuguese infants: The Upper Project. (30th September 2020) - Costa de Miranda, R; Rauber, F; Moraes, M; Torres, D; Lopes, C; Rodrigues, S; Bertazzi Levy, R
Abstract: Background: The dietary share of ultra-processed foods (UPF) has been associated with low diet quality, including high content of free sugar, mainly in adults' populations. We aim to assess the influence of UPF consumption on free sugar intake of Portuguese infants. Methods: Cross-sectional representative study including 573 infants (6-23 months old) who participated in the 2015-2016 National Food, Nutrition and Physical Activity Survey. Dietary intake was collected by two non-consecutive food diaries (time interval 8-15 days). Food items were classified according food processing degree by the NOVA system. Total energy intake and percentage provided by each NOVA food groups as well as the free sugar content of the overall diet were assessed. Mean free sugar intake was evaluated across quintiles (Q) of UPF consumption by linear regression adjusted for socioeconomic covariates. Results: Mean energy intake was 935 kcal/day, in which 49.1% was derived from unprocessed/minimally processed foods, 7.2% from processed culinary ingredients, 7.0% from processed foods and 36.6% from UPF. The mean dietary share of UPF ranged from 12.5% (Q1) to 65.5% (Q5) of total energy. Within UPF, infant formulas (19.3%), milk-based drinks (6.7%) and sweet snacks (4.8%) contributed the most to energy intake. Mean free sugar intake in the overall diet accounted for 8.1% of total energy intake, in which 92.5% came from UPF. As the UPF consumption increased, the dietary content of free sugar increased significantly (β = 0.77; p < 0.001). Contribution of free sugar in total energy intake raised from 2.9% to 12.7%, representing an increment of 338% from the lower to the upper quintile of the dietary share of UPF. Conclusions: Portuguese infants had an important intake of free sugar. Nearly all of this intake came from UPF, which calls for public health efforts to avoid UPF consumption by this population group. Funding: FAPESP 2018/07391-9, 2019/05972-7 (MCR), 2016/14302-7 (FR); POCI-01-0145-FEDER-032090. Key messages: Ultra-processed foods contributed with 36.6% of total energy intake and 92.5% of free sugar in the diets of Portuguese infants. As the ultra-processed foods consumption increased, the dietary content of free sugar increased significantly from 2.9% (Q1) to 12.7% (Q5), representing an increment of 338%.